2019
DOI: 10.1177/2515690x19886276
|View full text |Cite
|
Sign up to set email alerts
|

Investigating In Vitro Antibacterial Activities of Medicinal Plants Having Folkloric Repute in Ethiopian Traditional Medicine

Abstract: Medicinal plants are targeted in the search for new antimicrobial agents. Nowadays, there is an alarmingly increasing antimicrobial resistance to available agents with a very slow development of new antimicrobials. It is, therefore, necessary to extensively search for new agents based on the traditional use of herbal medicines as potential source. The antibacterial activity of 80% methanol extracts of the leaves of Verbena officinalis (Vo-80ME), Myrtus communis (Mc-80ME), and Melilotus elegans (Me-80ME) was te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
4
15
0
Order By: Relevance
“…Records from as far back as the fifteenth century detail traditional medical practices and remedies obtained from oral tales, early medico-religious manuscripts, and traditional pharmacopeia ( Jima and Megersa, 2018 ). The antimicrobial activities of these traditional medicinal plants are based on their secondary metabolites such as alkaloids, terpenoids, flavonoids, tannins and glycosides ( Sisay et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Records from as far back as the fifteenth century detail traditional medical practices and remedies obtained from oral tales, early medico-religious manuscripts, and traditional pharmacopeia ( Jima and Megersa, 2018 ). The antimicrobial activities of these traditional medicinal plants are based on their secondary metabolites such as alkaloids, terpenoids, flavonoids, tannins and glycosides ( Sisay et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The agar well diffusion assay has been used in this research because it is more sensitive than the agar disc diffusion assay (Valgas et al, 2007). Many studies have shown that extracts obtained from the Euphorbia and Melilotus genera inhibit the growth of different microorganisms at various concentrations (Annapurna et al, 2004;Singh & Kumar, 2013;Sonju et al, 2017;Sisay et al, 2019). Other studies on the species of genus Euphorbia and Melilotus have confirmed the efficacy of the methanolic extracts compared with the aqueous extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing drug resistance has led researchers to try to find alternative or complementary herbal medicines to inhibit the growth of these pathogens, and many studies have been conducted in this area. A study by Sisay et al (2019) showed that the extract of Myrtus significantly reduces the growth inhibitory zone diameter of P. aeruginosa in laboratory (28). The results of another study carried out by Chakotiya et al (2016) on Glycyrrhiza glabra exhibited the effective role of this plant's extract on inhibiting the growth of P. aeruginosa clinical isolates (29).…”
Section: Discussionmentioning
confidence: 96%